Degradation of Quercetin and Luteolin by Eubacterium ramulus - Braune, Annett (American Society for Microbiology, 2001)
The degradation of the flavonol quercetin and the flavone luteolin by Eubacterium ramulus, a strict anaerobe of the human intestinal tract, was studied. Resting cells converted these flavonoids to 3,4-dihydroxyphenylacetic acid and 3-(3,4-dihydroxyphenyl)propionic acid, respectively. The conversion of quercetin was accompanied by the transient formation of two intermediates, one of which was identified as taxifolin based on its specific retention time and UV and mass spectra. The structure of the second intermediate, alphitonin, was additionally elucidated by (1)H and (13)C nuclear magnetic resonance analysis. In resting-cell experiments, taxifolin in turn was converted via alphitonin to 3,4-dihydroxyphenylacetic acid. Alphitonin, which was prepared by enzymatic conversion of taxifolin and subsequent purification, was also transformed to 3,4-dihydroxyphenylacetic acid. The coenzyme-independent isomerization of taxifolin to alphitonin was catalyzed by cell extract or a partially purified enzyme preparation of E. ramulus. The degradation of luteolin by resting cells of E. ramulus resulted in the formation of the intermediate eriodictyol, which was identified by high-performance liquid chromatography and mass spectrometry analysis. The observed intermediates of quercetin and luteolin conversion suggest that the degradation pathways in E. ramulus start with an analogous reduction step followed by different enzymatic reactions depending on the additional 3-hydroxyl group present in the flavonol structure.